An overview of Intermetallic Nickel Aluminides (Ni3Al) as an alternative Automotive Body Material - Ganesh Kumar, K.; Sivarao, Subramonian; T., Joseph Sahaya Anand (Universiti Teknikal Malaysia Melaka, 2010)
Better handling, be lighter, more fuel efficient and cause less pollution are some key requirement of a car in near future. One key technical strategy to achieve all this is the light weighting. The enormous potential of intermetallics especially aluminides as a light weight material in addition with many attractive properties, such as high oxidation and corrosion resistance and relatively low densities, combined with their ability to retain strength and stiffness at elevated temperatures make it's an ideal choice as an automotive body material. In considerations of all above, the aim of the present work is to alternate automotive body material with intermetallic Nickel Aluminides through its mechanical characteristics. The prime focus will be on to obtain the mechanical properties such as tensile, toughness and hardness which were tested using Universal Testing Machine (UTM), Impact tester, and Hardness Tester respectively. Crystallographic studies of these alloy material were carried out using X-ray diffraction (XRD) analysis. Microstructural properties and composition of these alloys were examined by Scanning Electron Microscopy (SEM)/ Energy Dispersive X-ray Spectrum (EDX). Heat treatment (annealing) and Tafel extrapolation tests were carried out for thermal and corrosion properties of this nickel aluminides alloy respectively.